Battery management system enhancement for lithium-ions battery cells using switched shunt resistor approach based on finite state machine control algorithm - Hussien, Shimaa A.; BaQais, Amal; Al-Gabalawy, Mostafa (Frontiers in Energy Research, 2023)
Due to their favorable characteristics, lithium-ion batteries have a dominant share of the battery market. There are a number of issues related to the use and management of Lithium-ion batteries in this paper, specifically with regard to the safe operation of the batteries as well as methods for balancing their cells. With the help of a passive cell balancing algorithm and a cell measurement circuit, a battery management system with a passive cell balancing algorithm has been developed. The purpose of this paper is to improve the efficiency of the balancing algorithm by implementing and analyzing a cell modelling method from the literature, with the aim of improving its performance. The results of this study showed that the use of the cell modelling system was able to improve the balancing algorithm’s balancing and charging times by 12.6%. Further, to validate the results obtained from the measurement system and the cell modelling system, an analysis was conducted of uncertainty propagation in order to validate the results. As part of future research, broader testing conditions may be used in order to better understand the positive impact of the cell modelling system on the balancing algorithm in the future.